Analisis Kinerja Protokol Routing Destination Sequenced Distanced Vector (DSDV) terhadap Serangan Blackhole dan Grayhole pada Mobile Ad Hoc Network (MANET) - Made Ayu Gayatri Widhiastuti; Dany Primanita Kartikasari; Aditya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Technological advances make network infrastructure also increasingly developed. One example of the development of network infrastructure is the existence of wireless network technology or Ad-Hoc network. MANET is one type of Ad-Hoc network that has a flexible network topology and nodes on MANET can freely move places. Nodes in MANET that can move around, become vulnerable to security attacks that can threaten network performance in MANET. Blackhole and grayhole attacks are attacks on MANET. In this study using Destination Sequenced Distanced Vector (DSDV) routing protocol that is proactive with random waypoint mobility to determine the performance of the protocol against blackhole and grayhole attacks. The study was conducted using NS2.35 simulation and scenarios in the form of variations in the number of normal nodes and attacker nodes. Testing is done by using QoS parameters such as packet delivery ratio, average end-to-end delay, throughput and normalized routing load. The test results showed that there was a decrease in the performance of the DSDV protocol before and already Blackhole and grayhole attacks based on certain QoS parameter values.